Specific characteristics of speed skating: implications for summer training - de Boer, R. W.; Ettema, G.; Faessen, B. G.; Krekels, H.; Hollander, A. P.; de Groot, G.; van Ingen Schenau, G. J. (Medicine & Science in Sports & Exercise, 1987)
14 well-trained speed skaters performed all-out exercise tests during ice speed skating, low walking (walking-like movement in skating position), and dry skating (side-to-side deep sitting push-offs). These dry-land activities are popularly used during the summer period. 1.Physiologically (VO2max) low walking was the same as skating but dry skating was significantly less demanding (62 ml/kg versus 48 ml/kg). 2.The biomechanical aspects were vastly different in both auxiliary activities (aspects of the leg actions in low walking and the convulsive leg actions in dry skating). It was concluded that neither low walking nor dry skating can be considered as specific training activities for speed skaters. There are no valuable training effects that will enhance speed skating from the enactment of these activities. They are useless activities for competent skaters. They could even be counter-productive if emphasized too heavily (probably would cause disruption of high-level neuromuscular patterns). Implication: One can analogize to other activities, for example, rowing and swimming, where exercises are practiced considerably. Such exercises are of no use to advanced athletes and have the potential to be harmful.